PSYCHOLOGICAL WELL-BEING AS A CORRELATE OF SOCIAL COMPETENCE OF TEACHER TRAINEES OF DISTANCE EDUCATION IN HIMACHAL PRADESH - Dr. Ritika Sharma; Bharti Sharma (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This research study aims to examine the relationship between social competence and psychological well-being of teacher trainees of distance education in Himachal Pradesh. Descriptive method of research was followed in this study. A sample of 60 B.Ed. students (Males= 23 and females= 37) enrolled in distance education program in Himachal Pradesh was selected. Psychological well-being scale by Sisodia & Choudhary (2012) and social competence scale by Sharma & Rani (2013) were administered to obtain the psychological well-being and social competence scores. Two-way analysis of variance (Psychological well-being x gender: 3 x2) was applied. The results of this study revealed higher levels of social competence among teacher trainees. The findings also showed that there exist no significant mean differences in social competence of low, average and high psychological well-being groups of teacher trainees. There was no significant gender difference in social competence of teacher trainees. There was no significant interaction effect of psychological well-being with gender on social competence of teacher trainees. However, it may be pointed out from the mean scores that the social competence is high in case of high psychological well- being and it seems to be better as compared to their average and low psychological well-being counterparts across gender groups of teacher trainees.